ナンキョク ニ オケル ソレン シン ムジン ジリョクケイ モウ ニ ヨリ エラレタ ショキ ケッカ - Papitashvili, V.O.; Zaitzev, A.N. (1986)
P(論文) この10年間に, 磁気経度110°線に沿って南極のpolar cap領域を通る無人観測網の観測が成功した。1978-1979年の南極夏季に収録された地磁気変化に関する初期解析結果が得られた。その結果, 南半球polar cap内の電離層など価電流系と惑星間空間磁場との関係は北半球のpolar cap内の電流系と類似している。しかし, この磁力計網観測は, 南半球polar cap内の電流系と惑星間空間磁場B_z, B_y成分との関係に関して新しい事実を与えた。この新しい事実を解釈するために, 新しく沿磁力線電流モデルの導入を思索した。 During the last decade the unmanned magnetometer network across the southern polar cap along geomagnetic meridian 110°between corrected geomagnetic latitudes -75 and -89°has been successfully operated. Initial results of the analysis of geomagnetic variations for the austral summer of 1978-1979 have been obtained. The global features of the southern polar cap equivalent ionospheric current systems related to the interplanetary magnetic field (IMF) are similar to the northern polar cap patterns. Scanning by the meridian magnetometer chain of the southern polar cap revealed a new peculiarities in the current systems related to the B_z and B_y components of the IMF. For the explanation of these peculiarities a new model of the field-aligned currents was speculated. departmental bulletin paper